Comparative study of SCFA and butyrate levels in chronic hepatitis versus cirrhosis patients - Mustika, Syifa; Fachrurrezza, Mochammad; Rakhmadhan, Iraky; Adam, Adam; Reyhan , Muhammad (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Cirrhosis is a common complication of chronic liver disease and exerts a profound influence on gut microbiota and metabolic function. Short-chain fatty acids (SCFAs), particularly butyrate, are crucial to intestinal integrity and immunomodulation. The relationship between SCFA levels and the progression of liver disease is not well understood. OBJECTIVES: The current study aimed to study the level of SCFAs and butyrate in fecal samples of patients with chronic hepatitis B, chronic hepatitis C, and compensated cirrhosis. METHODS: The research was conducted at Dr. Saiful Anwar General Hospital, Malang, Indonesia, from January to June 2023. Fecal samples were collected and measured for SCFA and butyrate concentrations by gas chromatography. The comparison was made statistically by the Mann-Whitney U test between groups. RESULTS: A total of 26 patients with chronic hepatitis B, chronic hepatitis C, or compensated cirrhosis were enrolled in the study. The overall mean SCFA level in the participants was 9.85 ± 4.78 mg/mL. The findings revealed no difference in the level of SCFA in chronic hepatitis patients and cirrhosis patients (p = 0.72). Likewise, there was no difference in butyrate levels between the two groups (p = 0.37). CONCLUSION: During the present study, SCFA and butyrate levels were not significantly different in chronic hepatitis patients compared to cirrhosis patients. SCFA synthesis and use may be affected by various factors such as dietary patterns, microbiota diversity, and metabolic differences among individuals. Further studies with larger populations and dietary control are necessary to delineate the role of SCFAs in the pathogenesis of liver disease and therapeutic applications.